Prognostic factors for cerebral palsy and motor impairment in children born very preterm or very low birthweight: a systematic review. (10th February 2016) - Linsell, Louise; Malouf, Reem; Morris, Joan; Kurinczuk, Jennifer J; Marlow, Neil
Abstract : Aim: There is a large literature reporting risk factor analyses for poor neurodevelopment in children born very preterm (VPT: ≤32wks) or very low birthweight (VLBW: ≤1250g), which to date has not been formally summarized. The aim of this paper was to identify prognostic factors for cerebral palsy (CP) and motor impairment in children born VPT/VLBW. Method: A systematic review was conducted using Medline, Embase, and Pyscinfo databases to identify studies published between 1 January 1990 and 1 June 2014 reporting multivariable prediction models for poor neurodevelopment in VPT/VLBW children (registration number CRD42014006943). Twenty‐eight studies for motor outcomes were identified. Results: There was strong evidence that intraventricular haemorrhage and periventricular leukomalacia, and some evidence that the use of postnatal steroids and non‐use of antenatal steroids, were prognostic factors for CP. Male sex and gestational age were of limited use as prognostic factors for CP in cohorts restricted to ≤32 weeks gestation; however, in children older than 5 years with no major disability, there was evidence that male sex was a predictive factor for motor impairment. Interpretation: This review has identified factors which may be of prognostic value for CP and motor impairment in VPT/VLBW children and will help to form the basis of future prognostic research. What this paper adds: Strong evidence that intraventricular haemorrhage and periventricular haemorrhage are robust prognostic factors for cerebral palsy (CP). Some evidence that use of postnatal steroids increases risk of CP and that use of antenatal steroids is a protective factor. Gestational age was of limited use as a prognostic factor for CP in cohorts restricted to ≤32 weeks, likely due to reduced discriminatory power in very preterm subgroups and confounding with other important clinical events which are more strongly causally related. Moderate evidence that male sex is prognostic for motor impairment at school age in children free of major disability. This article is commented on by O'Shea on pages531–532 of this issue.